The Recent Trade Performance Of Sub-Saharan African Countries : Cause for Hope or More of the Same? - Ng, Francis; Yetes, Alexander J. (World Bank, Washington, DC, 2012)
This study examines empirical information for major Sub-Saharan African countries and provides an analysis of whether recent trade and economic policy changes by some Sub-Saharan African (SSA) countries enhanced their international competitiveness and improved their export performance. Specifically, it addresses the following points: (i) have recent exports from the Sub-Saharan African countries recently grown at a relatively faster pace and now come close to matching the average growth in world trade? (ii) Studies show Sub-Saharan African countries have been increasingly marginalized in world trade, as reflected in secular declines in their shares of this exchange and in shares of their major traditional exports (Ng and Yeats 1997). Does the available evidence indicate these trends have been reversed? (iii) Aggregate analyses of the composition of African countries' exports typically reveals a structure often held to be detrimental to industrialization and growth. African exports are typically concentrated in a relatively few primary commodities whose unstable prices (and export revenues) are thought to make development planning difficult. Does the available evidence indicate that shifts are occurring in the structure of exports toward products (like labor-intensive manufactures) that could play a more positive role in improving the prospects for industrialization and growth? (iv) Are positive micro-level changes occurring which are not reflected in aggregate trade statistics? Specifically, is the "revealed" comparative advantage of the SSA countries changing, has their competitive position improved (as reflected in changes in their market shares for traditional exports), or have they made progress in shifting the composition of exports up commodity processing chains? (v) Some studies of factors that influence the success or failure of efforts to promote industrialization and growth conclude a high level of intra-industry trade plays an important positive role. Related studies show that cross-country production sharing, which often involves a special type of intra-industry trade, assists participating countries to integrate into global and regional markets and may also act as a catalyst to industrialization and growth. Does the evidence suggest that the level of this trade has increased in African countries? (vi) Studies suggest there may be adverse consequences (like paying higher prices for imports and receiving lower prices for exports-see Hirschmann (1948), Avramovic (1979) or Yeats (1981) among others)-for countries whose trade is highly concentrated on a geographic basis. Does the available evidence suggest that the African countries have been more successful in establishing new trade ties and penetrating non-traditional markets? And (vii) finally, what evidence exists with regard to the importance of self-imposed government and commercial restrictions in the SSA countries? Are current trade and other economic other policies which affect the general business environment still sufficiently onerous so as to constitute a major "drag" on African exports and growth?